13g-14-13g=-g-7

Simple and best practice solution for 13g-14-13g=-g-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13g-14-13g=-g-7 equation:



13g-14-13g=-g-7
We move all terms to the left:
13g-14-13g-(-g-7)=0
We add all the numbers together, and all the variables
13g-13g-(-1g-7)-14=0
We add all the numbers together, and all the variables
-(-1g-7)-14=0
We get rid of parentheses
1g+7-14=0
We add all the numbers together, and all the variables
g-7=0
We move all terms containing g to the left, all other terms to the right
g=7

See similar equations:

| p7−6=p7 | | 7=10/(2x+3)+5 | | -2b+20=-7b-20 | | 6(t-1)=9(t-4( | | -1-16d-15=-16d-16 | | 9(x+2)=-36+6x | | -9x-5=x-6x+27 | | 18p+p+4p-22p=17 | | 56+10x=32+6x | | 4w=48w= | | 1x-98=104 | | –u=–3u+8 | | 5y-29=3y+29 | | 1x+3=4x+30 | | 0=-2/3x+5/3 | | 5/4x+2=8 | | |3−x|−8=2 | | -4n+4=-7-4n | | 0.4n-19.94=9.81+2.9n | | 17b-13b+b-4=16 | | -6(x+7=)-12 | | v=52/86-51/86v | | -118=n-3(1+8n) | | -1-2j=-2j-1 | | 2q=-17+1q | | 12x+12=1+13x | | 13c-12c-1=15 | | -9-14d=-12d+19 | | 2(5x-1)=7+10x | | -20+7y-16=3y+20 | | 3/2x=19 | | t+3t-t=9 |

Equations solver categories